Жидкие углеводороды и нефтепродукты - Филиппов Л. П. Лев Петрович; Артамонов В. Г.; Воробьева Е. В.; Кравчун С. Н.; Шахпаронов М. И. Михаил Иванович (Москва, Изд-во МГУ, 1989)
Авт. указаны на обороте тит. л.